If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying U + 72 = -72 Reorder the terms: 72 + U = -72 Solving 72 + U = -72 Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + U = -72 + -72 Combine like terms: 72 + -72 = 0 0 + U = -72 + -72 U = -72 + -72 Combine like terms: -72 + -72 = -144 U = -144 Simplifying U = -144
| 10r^2+15rs+8rs+12s^2= | | x^3-20x^2-525=0 | | x-76=156 | | 9.55+17.9c=17.9c+9.55 | | 2n-31=3n | | 64t^6-48t^4-4t^2+3=0 | | (x)(x+5)=204 | | 64t^4-48t^4-4t^2+3=0 | | 11d=11d-8 | | 21x^2+13x-20=0 | | -84=-8+2(2-8k) | | 14-3z=-3z+14 | | a(-2ab)= | | 54x+27y=x | | f(4x)=4x^2-11 | | 15-7p=-17p-15+10p | | 14x+71x=x | | 2vw-2w= | | 12x-(5x-12)=1+6x | | f(x)=2x^2-3x-1 | | 9+13j=13j+2 | | a(a^2-2ab+b^2)= | | 2(x+2)x=6 | | 0.5x-y=2 | | -4+10t=-2-10t+20t | | (X+93)=4x | | 17(9-x)-5=52 | | 0=-4u+4u | | 10g-3=10g-2 | | 7x-28=4 | | 7x-28=48 | | -(1-8x)=31+4x |